Pengaruh media komik digital terhadap pemahaman keragaman musik Nusantara pada siswa kelas IV sekolah dasar - Devano Arya Fahreizy; Karsono Karsono; Peduk Rintayati (Universitas Sebelas Maret, 2025)
Abstract This study aims to determine the influence of digital comic media on students' understanding of the diversity of Indonesian music among grade VI elementary school students in Blora Kota District, Blora Regency. The research employs a quasi-experimental design. The population consists of all elementary schools in Blora Kota District, Blora Regency. The sample was determined using the cluster random sampling technique. Data were collected using a test method in the form of pretests and posttests. The hypothesis was tested using a t-test. The study results indicate that the use of digital comic media enhances students' understanding of the diversity of Indonesian music. Comics motivate students and help them understand material through images. This is evidenced by an increase in the average posttest score (86.590) compared to the average pretest score (68.409). Moreover, the significance value from the t-test is 0.000, which is less than 0.05, indicating a significant influence of the independent variable on the dependent variable.